Smart energy in opportunistic networks - Lamont, Robert (2017)
Delay tolerant networks (DTNs) are a type of opportunistic network where the communication within the network is based on irregular and intermittent contacts, as the assumption of a straight end to end path in a network is discarded. DTNs therefore can be useful in situations where connectivity is an issue. Following the open industry and academic problem surrounding the electricity redundancy that is approaching along with the strict production only of electrical, battery powered vehicles in the United Kingdom by 2040, this research project centres its study on the use of an opportunistic network with the use of the electrical vehicles. Due to the huge need for additional electricity as more and more electrical powered vehicles are being used, a supply and demand problem for the battery energy is developed. The research in this project focuses on finding a solution to this dynamic supply and demand issue, making use of an opportunistic network to enable communication between vehicles, and static roadside charging points, to in turn allow energy transfer and sharing to occur. An opportunistic network enables the energy resources to be shared around nodes in the network in a smart and opportunistic manner, making use of the nearest neighbour nodes and the most useful nodes in terms of transmission resources, therefore making the energy be shared in a smarter and more beneficial way. Through the in depth battery buffer design and implementation into the network, the experiments portray that the introduction of energy sharing between both vehicles and static charging units, over a period of 12 hours, demonstrate that the average energy over the nodes in the network is 7.4 times higher than without any energy shared. On average, after 12 hours, in a hybrid scenario allowing energy sharing from both vehicles and static charging units, the remaining energy in the vehicles batteries is 19%. These results show that this approach of energy sharing between electrical vehicles proposed in this research project is a feasible solution to the dynamic supply and demand problem centred on the national gird’s electricity issue.